Non-Sinusoidal Predictive Model of Premium Motor Spirit (PMS) in Nigerian Fuel Price Hike - Akpienbi I. O.; Bello M.I.; Atureta M.S.; Barde A. (Darul Yasin Al Sys, 2026)
This study investigates the dynamics of Premium Motor Spirit (PMS) prices in Nigeria using a non-sinusoidal high-order mathematical model applied to annual data spanning 1990–2022. The proposed modelling framework is designed to represent long-term price growth behaviour and structural progression rather than periodic or cyclical movements. Model parameters were estimated using the least squares estimation technique to ensure optimal fitting of the observed price series. The adequacy of the model was evaluated through validation error metrics and correlation analysis, providing quantitative measures of goodness-of-fit and predictive reliability. The findings indicate that the non-sinusoidal high-order model effectively represents the sustained upward trajectory of PMS prices over the study period, reflecting gradual economic adjustments, inflationary pressures, and long-term policy influences. However, deviations between observed and model-generated prices were evident during periods characterized by abrupt policy interventions, subsidy reforms, and regulatory shocks, which introduced short-term irregularities into the price structure. Despite these disturbances, the model maintained a strong capacity to describe the overall price evolution and underlying trend of PMS pricing in Nigeria. This study contributes to energy price modelling literature by demonstrating the relevance of non-sinusoidal growth-based approaches for analysing long-term energy price behaviour in regulated and policy-sensitive economic environments.